Kedudukan Hukum Majelis Rakyat Papua dan Ratio Decidendi Mahkamah Konstitusi: Studi Putusan Pengadilan - Fahri Bachmid (SIGn Jurnal Hukum, 2021)
This study aims to analyze the legal standing and interest of the MRP as an embodiment of asymmetrical decentralization policies and the ratio decidendi of the Constitutional Court in Decision Number 47/PUU-XIX/2021. This normative legal study uses the statute and case approaches and collects data through a literature study technique. Results showed that asymmetrical decentralization policy prioritizes the specificity, uniqueness, diversity of regions, and unity of society through indigenous law and traditional rights. The granting of special autonomy to Papua aims to reduce disparities and improve living standards for the indigenous people. The MRP, established as a cultural representation with specific authority in protecting the rights of the indigenous people of Papua, evaluated that some provisions in Law Number 21 of 2001 and Law Number 2 of 2021 contradict the 1945 Constitution. In contrast, MRP’s request does not contain constitutional issues, and some are in line with the interests of the Local Government. In Decision 47/PUU-XIX/2021, the Constitutional Court stated that part of the complainant’s request could not be accepted and rejected the complainant’s request other than and the rest. Therefore, it is recommended that the MRP collaborate with the Local Government to promote the interests of the indigenous people of Papua. The Government must also continuously monitor the progress and evaluate the asymmetrical decentralization policy in reducing disparities and improving the standard of living for the indigenous people of Papua. Furthermore, the Government should ensure that the rights of the indigenous people of Papua remain protected and respected.